Fundamentals of motor behavior - Fairbrother, Jeffrey T. 1964- (Champaign, IL Human Kinetics, 2010)
Motor behavior is a fascinating field of study with real-world applications in a variety of careers. Fundamentals of Motor Behavior provides students with an excellent introductory-level look at the goals and opportunities in this exciting area. Engaging and reader-friendly, the text will enable those with little or no background in motor behavior to see the objectives that researchers and practitioners in the field pursue, the career options available, and the education required for pursuing a career in the field. One of the many strengths of Fundamentals of Motor Behavior is its focus on the real-world application of the information presented. The text takes concepts taught in advanced motor behavior courses and shows how they are relevant to everyday living. With this approach, even students who know nothing about motor behavior will feel comfortable learning new terms and material. The text begins by defining what motor behavior is and what students can do with it, including various academic and professional career paths. It then discusses the concepts and principles of motor behavior that form the foundation of knowledge that students will need in order to pursue a career in the field. These building blocks include the process of observation, how people control their movements, ways people learn motor skills, the capabilities and limitations each person brings to a learning situation, and ways in which practice settings can be structured. The book closes with an inspiring vision of the future of motor behavior that will enable students to see how they may eventually fit into the field and contribute to it. The author takes advantage of a full array of reader-friendly elements to engage students in the ideas and help them understand how they apply in the real world: Chapter objectives outline the reader's goals for each chapter, and chapter summaries tie together the important points; Opening scenarios set the stage for the content to come; Technology highlight boxes feature applications that today's researchers and professionals are using to analyze movement and advance the field; Skill Insights draw readers into the material by posing "did you know?" types of questions and revealing some surprising information; Success Stories highlight how researchers and professionals apply their knowledge of motor behavior to their jobs and explore possible career paths; An appendix includes checklists for using the material in various professional settings, which reinforces the real-world application of the concepts. This entertaining book is part of Human Kinetics' Fundamentals of Sport and Exercise Science series. The series helps students and professionals understand the basic topics, goals, and applications of the subdisciplines in kinesiology. This and other books in the series are not intended to provide in-depth knowledge of the field, but rather to provide a solid grounding that readers can use as a jumping-off point for further study.
Series Preface -- Preface -- Acknowledgments -- Part I. Welcome to Motor Behavior -- Chapter 1. What Is Motor Behavior? -- Research -- Practical Application -- Three Subdisciplines -- A Brief History of Motor Behavior -- Related Fields of Study -- The Short of It -- Chapter 2. What Can I Do With Motor Behavior? -- Academic Path -- Professional Paths -- A Side Path -- The Short of It -- Part II. Building Blocks of Motor Behavior -- Taking a Systematic Approach -- Accounting for the Person, the Task, and the Performance Setting -- Information Processing -- Chapter 3. Observing Behavior -- Closed and Open Skills -- Discrete, Serial, and Continuous Skills -- Observation: A Critical Key to Understanding Motor Behavior -- The Short of It -- Chapter 4. Understanding How We Control Movements -- Sources of Sensory Information -- Continuous Control -- No-Feedback Control -- Combining Continuous and No-Feedback Control -- The Short of It -- Chapter 5. Understanding How We Learn Motor Skills -- Theories of How We Learn -- Ways We Learn Motor Skills -- Transfer -- Feedback -- The Short of It -- Chapter 6. Capabilities and Limitations -- Information Processing -- Reacting Faster: Ways to Reduce the Time Spent on Information Processing -- How We Pay Attention -- What We Pay Attention to Makes a Difference -- Arousal and Performance -- Speed-Accuracy Trade-Offs -- Abilities and Skills -- The Short of It -- Chapter 7. Setting Practice Procedures -- Constant and Varied Practice -- Blocked and Random Practice -- Practice Distribution -- Deciding How to Design Practice -- The Short of It -- Chapter 8. Putting It All Together: The Motor Skill Learning Cycle -- Phase 1: Consider the Person, Task, and Performance Setting -- Phase 2: Plan for Practice -- Phase 3: Implement Practice -- Phase 4: Review the Overall Instructional Process -- The Short of It -- Epilogue: The Future of Motor Behavior -- Appendix A: Learn More About Motor Behavior -- Appendix B: Implementing Motor Behavior in the Real World -- References -- Bibliography -- Index -- About the Author
Includes bibliographical references
Keywords: Motor learning -- Textbooks